2013
DOI: 10.1093/infdis/jit261
|View full text |Cite
|
Sign up to set email alerts
|

Gametocyte Dynamics and the Role of Drugs in Reducing the Transmission Potential of Plasmodium vivax

Abstract: Background. Designing interventions that will reduce transmission of vivax malaria requires knowledge of Plasmodium vivax gametocyte dynamics.Methods. We analyzed data from a randomized controlled trial in northwestern Thailand and 2 trials in Papua, Indonesia, to identify and compare risk factors for vivax gametocytemia at enrollment and following treatment.Results. A total of 492 patients with P. vivax infections from Thailand and 476 patients (162 with concurrent falciparum parasitemia) from Indonesia were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 50 publications
5
47
0
Order By: Relevance
“…However, for patients with recurrent asexual parasitemia between day 7 and day 42, 53.57% had patent gametocytemia. The propensity of gametocyte carriage during recurrence is consistent with findings from earlier clinical trials (43). Thus, it is important that therapies for vivax malaria effectively clear both the blood and liver stages, so as to prevent recurrences (recrudescence and relapse), as well as the associated gametocytes.…”
Section: Discussionsupporting
confidence: 75%
“…However, for patients with recurrent asexual parasitemia between day 7 and day 42, 53.57% had patent gametocytemia. The propensity of gametocyte carriage during recurrence is consistent with findings from earlier clinical trials (43). Thus, it is important that therapies for vivax malaria effectively clear both the blood and liver stages, so as to prevent recurrences (recrudescence and relapse), as well as the associated gametocytes.…”
Section: Discussionsupporting
confidence: 75%
“…Detection of gametocytes, through pvs25 gene transcripts, in nearly all qPCR-confirmed P. vivax infections tested is somewhat surprising, since recent studies have found much lower proportions of gametocyte-positive infections in Southeast Asia [47], [48] and Papua New Guinea [49]. Since gametocytes comprise only 2% of circulating blood stages [50], microscopists are likely to miss gametocytes in population-based studies where low-density infections are often sampled [23].…”
Section: Discussionmentioning
confidence: 99%
“…It follows that asymptomatic P. vivax infection is relatively common even in low transmission settings [4]. Additionally, in contrast to P. falciparum gametocytes, P. vivax gametocytes arise early in infection and accompany the majority of symptomatic infections, though they have a relatively short lifespan, on the order of 3 days [32,12]. As with P. falciparum , submicroscopic gametocyte densities have also been shown to lead to mosquito infection [42].…”
Section: The Asymptomatic Reservoir Is Heterogeneous In Terms Of Persmentioning
confidence: 99%